THE EFFECT OF DISSOLVED BARIUM ON BIOGEOCHEMICAL PROCESSES AT COLD SEEPS - Aloisi G.; Wallmann K.; Bollwerk S.M.; Bohrmann G.; Suess E.; Derkachev A. (My University, 2004)
A numerical model was applied to investigate and quantify the biogeochemical processes fueled by the expulsion of barium and methane-rich fluids in the sediments of a giant cold-seep area in the Derugin Basin (Sea of Okhotsk). Geochemical profiles of dissolved Ba2+, Sr2+, Ca2+, SO42−, HS−, DIC, I− and of calcium carbonate (CaCO3) were fitted numerically to constrain the transport processes and the kinetics of biogeochemical reactions. The model results indicate that the anaerobic oxidation of methane (AOM) is the major process proceeding at a depth-integrated rate of 4.9 μmol cm−2 a−1, followed by calcium carbonate and strontian barite precipitation/dissolution processes having a total depth-integrated rate of 2.1 μmol cm−2 a−1. At the low seepage rate prevailing at our study site (0.14 cm a−1) all of the rising barium is consumed by precipitation of barite in the sedimentary column and no benthic barium flux is produced. Numerical experiments were run to investigate the response of this diagenetic environment to variations of hydrological and biogeochemical conditions. Our results show that relatively low rates of fluid flow (<~5 cm a−1) promote the dispersed precipitation of up to 26 wt% of barite and calcium carbonate throughout the uppermost few meters of the sedimentary column. Distinct and persistent events (several hundreds of years long) of more vigorous fluid flow (from 20–110 cm a−1), instead, result in the formation of barite-carbonate crusts near the sediment surface. Competition between barium and methane for sulfate controls the mineralogy of these sediment precipitates such that at low dissolved methane/barium ratios (<4–11) barite precipitation dominates, while at higher methane/barium ratios sulfate availability is limited by AOM and calcium carbonate prevails. When seepage rates exceed 110 cm a−1, barite precipitation occurs at the seafloor and is so rapid that barite chimneys form in the water column. In the Derugin Basin, spectacular barite constructions up to 20 m high, which cover an area of roughly 22 km2 and contain in excess of 5 million tons of barite, are built through this process. In these conditions, our model calculates a flux of barium to the water column of at least 20 μmol cm−2 a−1. We estimate that a minimum of 0.44 × 106 mol a−1 are added to the bottom waters of the Derugin Basin by cold seep processes, likely affecting the barium cycle in the Sea of Okhotsk.